In vitro dynamic phenotyping for testing novel mobilizing Agents - Tanaka, Motomu (Stem cell mobilization, 2019)
A new method to quantify the influence of mobilization agents on the dynamics of human hematopoietic stem and progenitor cells (HSPC) is introduced. Different from the microscopy-based high-content screening relying on multiple staining, machine learning, and molecular-level perturbation, the proposed method sheds light on the “dynamics” of HSPC in the presence of extrinsic factors, including SDF1α and mobilization agents. A well-defined model of the bone marrow niche is fabricated by the deposition of planar lipid membranes on glass slides (called supported membranes) displaying ligand molecules at precisely controlled surface densities. The dynamics of human HSPC, CD34+ cells from umbilical cord blood or peripheral blood, are monitored by time-lapse, live cell imaging with a standard phase-contrast microscopy or a specially designed microinterferometry in the absence or presence of mobilization agents. After extracting the contour of each cell, one can analyze the dynamics of cell “shapes” step-by-step, yielding various levels of information ranging from the principal mode of deformation, the persistence of deformation patterns, and the energy consumption by HSPC in the absence and presence of mobilization agents. Moreover, by tracking the migration trajectories of HSPC, one can gain insight how mobilization agents influence the “motion” of HSPC. As these readouts can be connected to a theoretical model, this strategy enables one to classify the influence of not only mobilization agents but also target-specific inhibitors or other treatments in quantitative indices.
Gesehen am 16.04.2020